Change of Direction Speed Tests in Basketball Players: A Brief Review of Test Varieties and Recent Trends - Takashi Sugiyama; Sumiaki Maeo; Toshiyuki Kurihara; Hiroaki Kanehisa; Tadao Isaka (Frontiers Media S.A., 2021)
Change of direction speed (CODS) is essential for basketball performance, extensively assessed by various tests. This review aimed to summarize the CODS test varieties for basketball players on publications until 2019 and identify recent trends regarding what types of tests have gained attention in the 2010s. Electronic literature searches were conducted using three databases with relevant keywords. 104 studies were found eligible, conducting CODS tests 159 times in total with 48 test varieties. To facilitate distinctions between the tests, each test was categorized into one of three types based on the distinctive movement characteristics and changing angles as follows: Defensive (involving lateral shuffling), 180°-turn (exerting only 180°-turns), and Cutting (performing diagonal- or side-cut). We then counted the number of publications and adopted times reported per year for each test, and calculated the adoption rate for each categorized test type. The first CODS test performed in basketball players was the T-Test, reported in 1991, and this was the most commonly adopted test (44/159 times). The 2010s saw abrupt increases in the number of publications (1990s-2000s-2010s: 5-9-90) and test varieties (4-7-44). The adoption rates in the 2010s were similar among the three types (i.e., Defensive/180°-turn/Cutting: 37%/30%/33%), with the Cutting type gradually increasing over the last three decades (1990s-2000s-2010s: 0%-9%-33%). These results suggest that while CODS performances in basketball players are increasingly studied with various tests, recent studies give equal weight to all of the three categorized test types, with increasing adoption of the Cutting type, to assess specific CODS performances.